Optimizing Teacher Performance through POAC-Based Principal Supervision: A Managerial Analysis of Elementary Schools in Cisurupan Garut - Wawan Ruswandi; N. Dede Khoeriah (At Turots: Jurnal Pendidikan Islam, 2026)
This study explores the management of principal supervision in enhancing teacher performance at SDN 2 and SDN 3 Cisurupan Garut through the analytical application of the POAC framework Planning, Organizing, Actuating, and Controlling. Employing a qualitative descriptive method, data were collected through in-depth interviews, direct observations, and documentation analysis. The findings reveal that systematic and participatory planning facilitated adaptive teaching strategies aligned with teachers’ professional needs; effective organizing fostered collaborative supervision structures that strengthened communication and accountability; actuating, operationalized through mentoring and reflective dialogue, stimulated innovation and professional engagement; and continuous controlling ensured feedback-driven improvements in teaching quality. Quantitative indicators demonstrated significant increases in teacher performance metrics across planning readiness, collaboration, reflective practice, and accountability. The study advances the theoretical and practical discourse on educational leadership by evidencing that an integrative, data-informed supervision model based on POAC principles can sustainably elevate teaching quality. This research further addresses gaps in prior studies by framing supervision not merely as an administrative obligation but as a strategic and holistic process grounded in leadership dynamics and professional growth.